A cost minimization analysis of the implementation of the international lung screening trial in Catalonia (Spain) - Rosell, Antoni; Baeza, Sonia; Mouriño, Rocío; Saigí, Maria; Munné, Marta; López de Castro, Pedro; Bechini, Jordi; Estrada, Oriol; Ara, Jordi; Ricou, Laura; López-Seguí, Francesc (BMC health services research, 2025)
Background NLST and NELSON trial showed that lung cancer mortality can be reduced by 20–24% using low-dose computed tomography screening, due to an increase in early-stage diagnoses. Research question How much lung cancer-related direct costs may be reduced using low-dose computed tomography screening based on the ILST-protocol in a public healthcare system? Methods Cost analysis of lung cancer screening vs. usual care in the framework of the retail price of the Catalan public healthcare system. The lung cancer screening group included costs of screening (ILST-protocol), treatment cost according to weighted average distribution of TNM staging in the NLST and NELSON trials, lung cancer detection rate and smoking-cessation intervention. The usual care group included treatment costs based on distribution of TNM staging registered in the Spanish index hospital. Results In the usual care group, treatment costs were €91,959. In 5-year of lung cancer screening program, the average expected costs per subject were €1,342 (range €1,054 − 1,832) for screening and €32,431 for treatment, with an expected reduction of €952 based on an average cancer detection rate of 1.6%. The decrease in cost resulting from the stage shift offsets 70.6% of the costs of the screening program. Conclusions The decrease in direct costs associated with lung cancer treatment due to a stage shift resulting from LCS of high-risk populations compensates for a substantial part of the LCS program costs. Trial registration Retrospectively registered.